Streptococcus pneumoniae associated hemolytic uremic syndrome in children - Young, Heather L.; Brown, Clare C.; Crawford, Brendan; Blaszak, Richard T.; Prodhan, Parthak (Frontiers in Pediatrics, 2023)
Previous small-scale, single-center investigations of Streptococcus pneumoniae associated hemolytic uremic syndrome (SpHUS) have shown increased disease severity among SpHUS relative to non-SpHUS patients. Our study compares the impact of S. pneumoniae on patient outcomes between SpHUS cases and non-SpHUS controls using the national, multicenter retrospective Pediatric Health Information Systems (PHIS) Database. Children <18 years of age with a diagnosis of HUS were included. Multivariable linear and logistic regressions were utilized to assess the impact of S. pneumoniae on mortality, length of stay (LOS), intensive care unit admission (ICU), and mechanical ventilation use. Three sets of models were conducted to adjust for 1) demographic characteristics, 2) demographic characteristics and organ systems, and 3) demographic characteristics and individual clinical conditions. Of 3,952 index HUS hospitalizations, 231 (5.8%) were due to SpHUS. In models adjusted for demographic characteristics, SpHUS patients had worse outcomes, including longer hospital stays, longer ICU length of stay, increased rate of ICU admission, increased mortality, and increased use of mechanical ventilation (p<0.05 for all). There was a strong positive relationship between clinical complications and adverse outcomes. After adjusting for organ systems, SpHUS was associated with increased odds of ICU admission (aOR: 1.75; 95% CI: 1.01, 3.00; p=0.044) and mechanical ventilation (aOR: 3.50; 95% CI: 2.15, 5.69; p<0.001). When adjusting for individual clinical conditions, SpHUS was associated with mechanical ventilation (aOR: 3.21 ; 95% CI: 1.81, 5.69; p<0.001). Our study highlights that SpHUS patients are at increased risk of multiple adverse outcomes likely due to the summative impact of pneumococcal infection and HUS as well as more frequent clinical complications.